Migración y redes sociales: discursos sobre la ayuda social hacia los migrantes venezolanos en contexto de pandemia por los usuarios peruanos en Twitter - Yalta Gonzales, Edgar Mauro (2021)
The COVID-19 pandemic has exposed and exacerbated the economic, health, political and social problems that exist in Peru. Among them, the issue of Venezuelan migration and its vulnerability during the pandemic has not been the exception. For this reason, a debate was generated, both among the population and in the media, regarding Venezuelan migrants and whether they should also receive social support from the State. In this article, our objectives are to analyze the discourses generated in their tweets by Peruvian users of the social network Twitter regarding the debate on social support for Venezuelan migrants, and to identify the strategies and resources used by users to elaborate these discourses. To do so, we selected an online survey proposed by the Twitter account of the news channel ATV+ Noticias and collected the most representative tweets from the comments section to elaborate the corpus. The results indicate that Peruvian users show a marked polarized position with a greater tendency to comment negatively on migrants.